Reading Aloud to Children, Social Inequalities, and Vocabulary Development: Evidence from a Randomized Controlled Trial - Carlo Barone; Denis Fougère; Karine Martel (Institute of Labor Economics (IZA), 2020)
This study presents the results of a randomized controlled trial assessing the impact of a shared-book reading (SBR) intervention that targeted children aged 4 living in socially mixed neighborhoods of the city of Paris. We selected a large, random sample of families and provided parents with free books, information on the benefits of SBR and tips for effective reading practices. We measured SBR frequency and children's vocabulary before and after this intervention, among treated and control children. The intervention had a large effect on SBR frequency. At the pre-test, SBR on a daily basis involved 41.2% of the families, and the treatment fostered this practice by 8 percentage points. SBR on a weekly basis was fostered by 14 percentage points. The intervention fostered SBR frequency only in low-educated households. This equalising impact is an important finding against the background of previous research reporting that disadvantaged families tend to benefit less from SBR programs. The intervention also significantly enhanced children's language skills measured with standardized tests of receptive vocabulary. The effect size for the main treatment effect ranges from 0.12 at the post-test to 0.16 at the follow-up. Treatment effects are persistent six months after the end of the intervention. Children from low-educated and immigrant families improved their vocabulary as much as those from high-educated, native families. Moreover, the persisting positive impacts on vocabulary growth detected at the follow-up also involve children from disadvantaged families. Furthermore, these children more often attend schools with lower educational resources. It is therefore encouraging that the intervention has strong impacts in schools with initially low involvement in reading-related activities and with low educational resources.
Keywords: I21; I24; J13; C93; 330; early childhood; language skills; parental reading; field experiment